Wastewater-based analysis of antimicrobial resistance at UK airports: Evaluating the potential opportunities and challenges - Knight, Margaret E.; Farkas, Kata; Wade, Matthew; Webster, Gordon; Pass, Daniel A.; Perry, William; Kille, Peter; Singer, Andrew; Jones, Davey L. (Environment international, 2025)
[Display omitted] •The resistome composition differed between airport terminals.•Flights from Asia carried more diverse resistomes than those from Europe.•Aircraft wastewater may introduce ARGs from global travellers into local systems.•Flight resistome clusters were not associated with geography.•Aircraft wastewater has potential for global AMR surveillance, despite some limitations. With 40 million annual passenger flights, airports are key hubs for microbial communities from diverse geographic origins to converge, mix, and distribute. Wastewater derived from airports and aircraft represent both a potential route for the global dispersion of antimicrobial resistant (AMR) organisms and an under-utilised resource for strengthening global AMR surveillance. This study investigates the abundance and diversity of antimicrobial resistance genes (ARGs) in wastewater samples collected from airport terminals (n = 132), aircraft (n = 25), and a connected wastewater treatment plant (n = 11) at three international airports in the UK (London Heathrow, Edinburgh and Bristol). A total of 76 ARGs were quantified using high throughput qPCR (HT-qPCR) while a subset of samples (n = 30) was further analysed by metagenomic sequencing. Our findings reveal that aircraft wastewater resistomes were compositionally distinct from those observed at airport terminals, despite their similar diversity. Notably, flights originating from Asia and Africa carried a higher number of unique ARGs compared to those from Europe and North America. However, clustering of the ARG profile displayed no overall association with geography. Edinburgh terminal and pumping station wastewater had compositionally comparable resistomes to that of the connected urban wastewater treatment plant, though further research is needed to determine the relative contributions of the local population and international travellers. This study provides the first comprehensive investigation of AMR in wastewater from both aircraft and terminals across multiple international airports. Our results highlight aircraft wastewater as a potential route for cross-border AMR transmission and a valuable tool for global AMR surveillance. However, the findings also underscore the limitations and need for standardised approaches for AMR monitoring in airport environments, to effectively mitigate the global spread of AMR and enhance public health surveillance strategies.